Replacement and Immunomodulatory Activities of 20% Subcutaneous Immunoglobulin Treatment: A Single-Center Retrospective Study in Autoimmune Myositis and CVID Patients - Danieli, Maria Giovanna; Verga, Jacopo Umberto; Mezzanotte, Cristina; Terrenato, Irene; Svegliati, Silvia; Bilo, Maria Beatrice; Moroncini, Gianluca (Frontiers in Immunology, 2022)
Background Immunoglobulin (Ig) replacement therapy represents a life-saving treatment in primary antibody deficiencies. The introduction of subcutaneous Ig (SCIg) administration brings a major improvement in quality of life for patients, compared to the traditional intravenous administration. In recent years, an additional role has been proposed for Ig therapy for various inflammatory and immune-mediated diseases. Consequently, the use of SCIg has expanded from immunodeficiencies to immune-mediated diseases, such as polymyositis (PM) and dermatomyositis (DM). Given the rarity of these conditions, it is still difficult to evaluate the real impact of SCIg treatment on PM and DM, and additional data are constantly required on this topic, particularly for long-term treatments in real-life settings. Aim This study aimed to increase the knowledge about the anti-inflammatory and immunomodulatory effects of SCIg treatment for myositis. To this aim, a long-term evaluation of the effectiveness of 20% human SCIg treatment (20% SCIg, Hizentra®, CSL Behring) was carried out in patients with PM/DM in care at our Center. In addition, an evaluation of the 20% SCIg therapy in CVID patients was provided. This analysis, beside adding knowledge about the use of SCIg therapy in this real-life setting, was intended as a term of comparison, regarding the safety profile. Results Results support the beneficial effect and tolerability of long-term 20% SCIg therapy in PM/DM patients, reporting a significant improvement in creatine kinase levels, muscle strength, skin conditions, dysphagia, disease activity (MITAX score) and disability (HAQ-DI score). None of the patients reported systemic reactions. The duration of the reported local reactions was a few hours in 80% of the patients, and all resolved spontaneously. CVID patients reported an improvement in all the considered effectiveness parameters at the end of 20% SCIg therapy. The frequency of the adverse events reported by PM/DM patients was not different from what reported in CVID patients, where the use of SCIg therapy is more consolidated Conclusions This study suggests that 20% SCIg treatment represents a viable and safe treatment for PM/DM patients and a valid therapeutic alternative to IVIg, with important advantages for patients’ quality of life.